Coherent orbital waves in the photo-induced insulator-metal dynamics of a magnetoresistive manganite. - Polli, D; Rini, M; Wall, S; Schoenlein, R; Tomioka, Y; Tokura, Y; Cerullo, G; Cavalleri, A (2007)
Photo-excitation can drive strongly correlated electron insulators into competing conducting phases, resulting in giant and ultrafast changes of their electronic and magnetic properties. The underlying non-equilibrium dynamics involve many degrees of freedom at once, whereby sufficiently short optical pulses can trigger the corresponding collective modes of the solid along temporally coherent pathways. The characteristic frequencies of these modes range between the few GHz of acoustic vibrations to the tens or even hundreds of THz for purely electronic excitations. Virtually all experiments so far have used 100 fs or longer pulses, detecting only comparatively slow lattice dynamics. Here, we use sub-10-fs optical pulses to study the photo-induced insulator-metal transition in the magnetoresistive manganite Pr(0.7)Ca(0.3)MnO(3). At room temperature, we find that the time-dependent pathway towards the metallic phase is accompanied by coherent 31 THz oscillations of the optical reflectivity, significantly faster than all lattice vibrations. These high-frequency oscillations are suggestive of coherent orbital waves, crystal-field excitations triggered here by impulsive stimulated Raman scattering. Orbital waves are likely to be initially localized to the small polarons of this room-temperature manganite, coupling to other degrees of freedom at longer times, as photo-domains coalesce into a metallic phase.